Manajemen Risiko Divisi Sistem Informasi Perguruan Tinggi Dengan Framework COBIT 5 - Francis Anderson Kojongian; Mewati Ayub (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
In order to achieve the company goals, in Universitas Kristen Maranatha, Information system becomes the main tool and Information Technology infrastructure become the backbone in running the company business model, along with the increasing of portfolio application, number of Information Technology services and the amount of human resources. Universitas Kristen Maranatha requires an international standard instrument to measure several domains, both Manage and Operation domains, holistically. By implementing frameworks such as COBIT 5 or COBIT 5 for IT RISK, ISO 31000: 2018, the company is able to measure planning effectiveness, strategic policies implementation, IT service management measured by Service Level Agreement, monitoring and evaluation. In this research, there are 7 domains implemented as follows: EDM01-Ensure Governance Framework Setting and Maintenance, EDM03- Ensure Risk Optimization, AP002- Manage Strategy, APO09- Manage Service Agreements, AP012-Manage Risk, BAI01-Manage Programmes and Projects, BAI05- Manage Organizational Change Enablement.